Utilization of Metaverse Technology in Building Higher Education Positioning: A Marketing Strategy Perspective in the Education Sector - Ulfia, Lily; Fauziah, Sitti; Halid, Yusrifah (Li Falah: Journal of Islamic Economics and Business, 2025)
The use of Metaverse technology in higher education remains limited, despite its potential to enhance universities' competitiveness and positioning. This study aims to explore how Metaverse can improve the position and competitiveness of higher education institutions, particularly Islamic State Universities (PTKIN), and its impact on educational quality and accessibility. The study employs a descriptive qualitative approach, using case studies of Muhammadiyah University Yogyakarta (MCU) and IAIN Kendari, with data collected through field observations, interviews with university administrators and students, and relevant documentation. Data were analyzed using Miles and Huberman’s interactive analysis model. The study is based on the Theory of Education Marketing in the Digital Age, emphasizing the role of digital technology in building engagement, and the Resource-Based View (RBV), focusing on Metaverse as a strategic resource for universities. Findings indicate that while challenges in infrastructure and human resources exist, Metaverse technology can enhance universities’ position by offering immersive and interactive learning experiences. Its use in marketing, such as virtual campus tours, enables universities to reach a broader prospective student base, both domestically and internationally. The study highlights the need for universities to integrate Metaverse technology into their curricula and marketing strategies to remain competitive and relevant in the Society 5.0 era.